Personal hygiene health education improves knowledge and behavior of scabies prevention in adolescents at the Blitar Juvenile Detention Center - Jefry Arditya Arditya; Titik Juwariyah (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
Background: The prevalence of scabies in all community health centers in Indonesia is 5.6-12.9%, making it the third most common skin disease. Transmission is easier in crowded environments and with high social interaction, making Islamic boarding schools one of the vulnerable locations. Additional risk factors include the habit of sharing personal equipment, low awareness of hygiene, and limited sanitation facilities. Low awareness of hygiene is influenced by low knowledge of clean and healthy living behaviors. Objective: To identify improvements in knowledge and behavior in preventing scabies in adolescents. Method: This study uses a quasi-experimental pre-post test design without control, by taking the entire population as a sample. The respondents of this study were 172 adolescents living in the Blitar juvenile correctional institution dormitory. The instrument in this study was a questionnaire on knowledge and behavior in preventing scabies. Data were collected before and after Health Education using the lecture method. Results: Before health education, 124 respondents (72.5%) had poor knowledge, while 47 respondents (27.5%) had sufficient knowledge. After treatment, 157 respondents (91.8%) had good knowledge, while 14 respondents (8.2%) had sufficient knowledge and 154 respondents (90.1%). Before treatment, 7.0% of respondents had sufficient behavior and 2.9% had good behavior. After treatment, 88.9% of respondents had good behavior and 11.1% had sufficient behavior. Conclusion: Regular health education is important to provide to prevent scabies at the Blitar Children's Correctional Institution